(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The achievement of a culture of cybersecurity is not possible through dissemination actions, even when necessary, but requires a huge specialized training work that takes into account in the process of teaching / learning to all sectors of society. It requires building a culture of cybersecurity inserted into a culture of safety and defense to involve in it the whole society. It is necessary to analyze previously key elements that build a strong culture of security and defense and then attend the specialized training in cybersecurity, especially at the university level.